Sample selection for models to represent ceramic cores fabricated by stereolithography three-dimensional printing. (10th September 2022) - An, X.L.; Liang, J.J.; Li, J.G.; Chen, J.W.; Zhou, Y.Z.; Sun, X.F.
Highlights: We believe that our study makes a significant contribution to the literature because the M2 layout was found to facilitate the SLA-3DP-based fabrication of high-mechanical-performance ceramic cores. An optimal high-temperature flexural strength of 24.2 MPa was achieved by the M2-based sample sintered at 1250 °C during casting heat treatment at 1550 °C. Essentially, a fundamental research-, evaluation-, and prediction-based framework of composition design, process optimization, and microstructure/property-defect analysis of SLA-3DP-derived ceramic cores was established through systematic characterization of high-throughput samples. Abstract: In this study, ceramic cores were fabricated by stereolithography three-dimensional printing (SLA-3DP) with excellent synthetic mechanical properties. To this end, green body samples were first three-dimensionally printed in three models, after which the samples were sintered at different temperatures. High-temperature flexural strengths of the ceramic core samples printed in model 2 reached a maximum value of 24.2 MPa at a sintering temperature of 1250 °C during casting heat test at 1550  °C. Meanwhile, the high- and room-temperature flexural strengths of ceramic core samples printed in model 2 were much stronger than those printed in models 1 and 3. Moreover, shrinkage, porosities, bulk densities and phase compositions of ceramic core samples printed in three models at different sintering temperatures did not show obvious differences. The ceramic core samples showed distinct mechanical properties as they had different fracture modes. We call this the "surface effect". The anisotropy flexural strength was induced by weak binding between layers. The recommended choice of sample for different models to represent ceramic cores fabricated by stereolithography three-dimensional printing is model 2. Herein, based on the results of systematic characterization of high-throughput samples, we report the basic research, evaluation and prediction system of composition design, process optimization, microstructure and property defect analysis of ceramic cores made of SLA-3DP.